Forest and Peatland Fire Dynamics in South Sumatra Province - Nurhayati, Ati Dwi; Hero Saharjo, Bambang; Sundawati, Leti; Syartinilia, Syartinilia; A. Cochrane, Mark (Forestry Faculty, Universitas Hasanuddin, 2021)
South Sumatra Province experiences forest and land fires every year. Peatland and human activity have caused this region to be more vulnerable to fire. In this study, we used annual mapping to describe the history of forest and land fires in Ogan Komering Ilir (OKI) District of South Sumatra to analyze fire trends during the 2015-2019 period. Hotspot data were obtained from Terra/Aqua MODIS satellite imagery at all confidence levels. Burned areas were identified using the Normalized Burn Ratio (NBR) Index, with data sources from Landsat 8 satellite imagery obtained from the USGS (United States Geological Survey). The highest number of hotspots were detected in 2015 (33,748), with 72% was located on peatland. Historical analysis of hotspot numbers, shows that the majority of burning occurs in September and October. This indicates that prevention activities must be carried out more intensively before these months. Linear regression between annual hotspot numbers and rainfall was not significant. Hotspots indicative of forest and land fire in OKI District were more influenced by human activities. The largest burned area (993,999 ha) occurred in 2015. The 2015 El Niño event triggered drought and worsened forest and land fires in Indonesia. Although no El- Niño conditions occurred in 2016-2018, fires continued to occur in OKI District, showing their independence from extreme drought. The fires occurring on peatlands burned a large area during 2015-2019 indicating that forest and land fires management must become a top priority in OKI District